Learning and peer feedback in shared online spaces - Thomas, Elaine; Rosewell, Jon; Kear, Karen; Donelan, Helen (Proceedings of the International Conference on Networked Learning, 2014)
Peer feedback, where students evaluate and give comments on each other's work, is a valued form of learning activity. Giving and receiving peer feedback, particularly if assessed, encourages students to engage with the assessment criteria and reflect on their work, promoting a deeper understanding. This paper introduces a project to investigate approaches to using peer feedback in shared online spaces, as part of distance learning courses. One approach uses a wiki, where students each contribute their work and other students provide evaluative comments and advice. The other approach uses OpenStudio, a 'studio' environment where students upload self-produced media objects, such as photographs and presentations, and comment on each other's work. Both approaches have produced high levels of student engagement. An initial examination of peer feedback in a wiki indicates that the quality of feedback is high, but students do not make as much use of it as they might. Survey results for a course using a studio (with feedback from peers but not tutors) reveals some students who, while they enjoy the sharing activities, believe they need 'expert' opinion. This project will evaluate these two approaches to online peer feedback in order to identify successful features in terms of (a) engaging students and (b) promoting student learning. The project will also identify areas for improvement. The first stage will map the uses of peer feedback in Computing and IT courses of the UK Open University. This stage will document: the educational objectives and intended learning outcomes of the activities; what students share and discuss in the activities; and, if the activities are assessed, how this is done. The second stage will evaluate the peer feedback activities in three courses which use online spaces for sharing and peer feedback. Data will be collected from students and tutors through focus groups and online surveys. The course forums will also be used to invite students to give their views. A qualitative analysis will be undertaken of online artefacts and interactions. Skills in evaluating the work of others and giving constructive feedback are important, both in education and beyond. This project will help develop these skills in online learning students. It will do this by generating case studies, investigating learning designs and proposing best practice guidelines for using and assessing online peer feedback.